Construction of the First SNP-Based Linkage Map Using Genotyping-by-Sequencing and Mapping of the Male-Sterility Gene in Leaf Chicory - Palumbo, Fabio; Qi, Peng; Pinto, Vitor Batista; Devos, Katrien M.; Barcaccia, Gianni (Frontiers in Plant Science, 2019)
We report the first high-density linkage map construction through genotyping-by-sequencing (GBS) in leaf chicory (Cichorium intybus subsp. intybus var. foliosum, 2n=2x=18) and the SNP-based fine mapping of the linkage group region carrying a recessive gene responsible for male-sterility (ms1). An experimental BC1 population, segregating for the male sterility trait, was specifically generated and 198 progeny plants were preliminary screened through a multiplexed SSR genotyping analysis for the identification of microsatellite markers linked to the ms1 locus. Two backbone SSR markers belonging to linkage group 4 of the available Cichorium consensus map were found genetically associated to the ms1 gene at 5.8 cM and 12.1 cM apart. A GBS strategy was then used to produce a high-density SNP-based linkage map, containing 727 genomic loci organized into 9 linkage groups and spanning a total length of 1,413 cM. 13 SNPs proved to be tightly linked to the ms1 locus based on a subset of 44 progeny plants analyzed. The map position of these markers was further validated by sequence-specific PCR experiments using an additional set of 64 progeny plants, enabling to verify that four of them fully co-segregated with male-sterility. A mesosynteny analysis revealed that 10 genomic DNA sequences encompassing the 13 selected SNPs of chicory mapped in a peripheral region of chromosome 5 of lettuce (Lactuca sativa L.) spanning about 18 Mbp. Since a MYB103-like gene, encoding for a transcription factor involved in callose dissolution of tetrads and exine development of microspores, was found located in the same chromosomal region, this orthologous was chosen as candidate for male-sterility. The amplification and sequencing of its CDS using accessions with contrasting phenotypes/genotypes (i.e. 4 male sterile mutants, ms1ms1, and 4 male fertile inbreds, Ms1Ms1) enabled to detect an INDEL of 4 nucleotides in its second exon, responsible for an anticipated stop codon in the male sterile mutants. This polymorphism was subsequently validated through allele-specific PCR assays and found to fully co-segregate with male-sterility, using 64 progeny plants of the same mapping BC1 population. Overall, our molecular data could be practically exploited for genotyping plant materials and for marker-assisted breeding schemes in leaf chicory.